1974
DOI: 10.1038/ki.1974.52
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline pharmacokinetics in the absence of renal function

Abstract: The Nijmegen Biomedical Study is a population-based cross-sectional study conducted in the eastern part of the Netherlands. As part of the overall study, we provide reference values of estimated glomerular filtration rate (GFR) for this Caucasian population without expressed risk. Age-stratified, randomly selected inhabitants received a postal questionnaire on lifestyle and medical history. In a large subset of the responders, serum creatinine was measured. The GFR was then measured using the abbreviated Modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

1975
1975
1992
1992

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 10 publications
2
25
0
Order By: Relevance
“…Concentrations in heart and lungs were always higher than in serum which corroborates Fabre's (8) and Cahen's results (19). The penetration of doxycycline into bronchial secretions has also been demonstrated in man (11,12,13) Hartnett (12) has shown that doxycycline remains in sputum for several days after the completion of treatment.…”
Section: Discussionsupporting
confidence: 74%
“…Concentrations in heart and lungs were always higher than in serum which corroborates Fabre's (8) and Cahen's results (19). The penetration of doxycycline into bronchial secretions has also been demonstrated in man (11,12,13) Hartnett (12) has shown that doxycycline remains in sputum for several days after the completion of treatment.…”
Section: Discussionsupporting
confidence: 74%
“…With the exception of absolute renal extraction, there was no correlation between lipophilicity and Doxycycline displayed a marked propensity to accumulate intraluminally in ileal segments containing milk. Such accumulation presumably is the result of the relatively high lipophilicity of doxycycline, permitting its passage across the intestinal mucosa, and its tendency to form complexes with polyvalent cations of metals (41); moreover, the observation is in accord with the finding that substantial amounts of doxycycline may be passively transported from the serum into the intestinal lumen of dogs (37), rats (38), and humans (41). Although the data of Table 1 suggest that doxycycline is somewhat less readily chelated by calcium than is oxytetracycline or tetracycline, other work indicates that at approximately neutral pH, the tetracyclines are almost completely chelated by all polyvalent metallic cations studied (1,2,4).…”
Section: Discussionsupporting
confidence: 73%
“…Many of these objectives have been met in minocycline and doxycycline (6,9,10,25,26,34,41). Of additional interest is the fact that neither of these tetracyclines appears to require a major adjustment in dose in the presence of renal failure (6, 41), suggesting that they are extensively eliminated by nonrenal routes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Doxycycline has several important advantages over other tetracycline analogues: absorption is almost complete (90-95%), tissue penetration, even if structurally modified by inflammation, is facile, elimination is slower, necessitating only one daily dose of 100 mg, and urine concentrations are higher yielding good results in the therapy of urinary tract infections (Schach von Wittenau & Delahunt, 1966;Fabre et al, 1967). Although 30% to 50% of administered doxycycline is normally excreted unchanged in the urine, it does not accumulate in cases of renal insufficiency and therefore has been extensively used in patients suffering from various degrees of renal impairment or even in anuric patients (Merier et al, 1969;Ritzerfeld et al, 1970;Whelton et al, 1974;Simon et al, 1975).…”
Section: Introductionmentioning
confidence: 99%